1998
DOI: 10.1021/jp980859r
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Orientations in Azopolymer Holographic Diffraction Gratings as Studied by Raman Confocal Microspectroscopy

Abstract: Optically isotropic films of an amorphous copolymer containing azobenzene moieties (pDR1M-co-MMA) were irradiated by interfering two circularly contrarotating polarized laser beams and permanent holographic diffraction gratings were prepared. These involve the formation of both birefringence and surface relief gratings. Using the Raman confocal microspectrometry, we have recorded various resonance enhanced polarized Raman spectra from the surface profile in order to get new insight into the orientational and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 47 publications
3
74
1
Order By: Relevance
“…At present, we can only speculate on the reason for the periodic adhesion variations. The most promising candidate is again the orientational distribution of chromophores, which results from competition between the light‐induced and flow‐induced orientations (Geue et al ., 1997; Lagugne‐Labarthet et al ., 1998). Depending on the preferential orientation at the particular local position, highly anisotropic azobenzene moieties can impose different attractive interactions onto the cantilever tip.…”
Section: Resultsmentioning
confidence: 99%
“…At present, we can only speculate on the reason for the periodic adhesion variations. The most promising candidate is again the orientational distribution of chromophores, which results from competition between the light‐induced and flow‐induced orientations (Geue et al ., 1997; Lagugne‐Labarthet et al ., 1998). Depending on the preferential orientation at the particular local position, highly anisotropic azobenzene moieties can impose different attractive interactions onto the cantilever tip.…”
Section: Resultsmentioning
confidence: 99%
“…For systems showing uniaxial symmetry, the order parameters P 2 and P 4 , the first two coefficients of the expansion in Legendre polynomials of the orientation distribution function, can be calculated by Raman spectromicroscopy (39,41,42). The method used is applicable to vibrational mode for which the Raman tensor is cylindrical.…”
Section: Orientationmentioning
confidence: 99%
“…Since there is no compelling argument to favor the Raman tensor of Pajcini et al (43) at the expense of that of Tsuboi et al (44), and since the orientation results are basically unaffected by the differences between the three tensors, we have decided to use the values of the order parameters obtained for a cylindrical Raman tensor, as done in previous studies (39,45). The calculation procedure is based on the measurement of four polarized spectra by Raman spectromicroscopy in the backscattering configuration (39,41,42). From these spectra, two intensity ratios for a given band…”
Section: For a Cylindrical Tensorþmentioning
confidence: 99%
“…They have shown that the orientation distribution of the chromophores varies spatially along the grating (i.e., whether on a hill, slope, or valley) and depends on the polarization combination used for the interfering beams. They concluded that the orientation of the chromophores is not only dictated by the spatially varying polarization of the incident irradiation but also by the mass transport of the polymer chains . They also reported differences in dye concentration between the hills and the valleys of an SRG .…”
Section: All‐optical Mass Transport Of Materialsmentioning
confidence: 99%